PENERAPAN PEMBELAJARAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION MATERI BANGUN RUANG SISI DATAR DI SMP - Yulia Harni Yanti; Edy Yusmin; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThis research aimed to know the effectiveness application of cooperative learning model with Group Investigation (GI) type in the polyhedron topic at class VIIIA SMP Negeri 19 Pontianak. The research method was ecperimen method with the research design was pre-experimental design. The subject of this research were 28 students at class VIIIA SMP Negeri 19 Pontianak. Based on the data analysis that review four aspects, the result are: (1) learning implementations cooperative learning model with Group Investigation (GI) type in the categorized very good with average score 3,52; (2) student’s learning actitivities cooperative learning model with Group Investigation (GI) type in the categorized active (68,51%); (3) student’s outcome reached classical completeness with 23 student (82,14%) of student can achieve the minimum completeness criteria; (4) student’s respond cooperative learning model with Group Investigation (GI) type in the categorize positive with 22 student (79%) give a very positive respond and 6 student (21%) give a positive respond. So, cooperative learning model with Group Investigation (GI) type effective apply to the polyhedron topic at class VIIIA SMP Negeri 19 Pontianak Keywords: Cooperative Learning Type Group Investigation, Effectiveness, Polyhedron